STRATEGI BAURAN PEMASARAN 7P DI CV. TANI ORGANIK MERAPI (TOM), KECAMATAN WUKISARI, KABUPATEN SLEMAN - Wafiq Nur Arbian; Epsi Euriga (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
This research discusses the implementation of the 7P marketing mix strategy at CV. Tani Organik Merapi is a company operating in the field of organic agriculture. This research also identifies the 7P marketing mix which includes product, price, promotion, place, people, process, and physical evidence, and how it is applied in the context of an organic farming company. This research aims to be able to analyze the SWOT to formulate an effective marketing strategy. The research results show that internal and external factors can influence a company, including strengths, weaknesses, opportunities and threats. This research method uses a mixed method by carrying out a research approach that combines quantitative and qualitative data analysis to obtain more comprehensive and accurate results. The analysis results show that CV's 7P marketing mix strategy. Merapi Organic Farming shows success in several aspects but requires improvement in the Promotion aspect. By using SWOT analysis, CV. Merapi Organic Farmers can develop 12 alternative strategies to improve performance and success in marketing organic vegetable products.